2018
DOI: 10.5505/turkhijyen.2018.22755
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Colchicine on Cell Cycle Arrest and MMP-2 mRNA Expression in MCF 7 Breast Adenocarcinoma Cells

Abstract: Amaç: Kolşisin, trisiklik alkaloid bir ilaç olup klinikte anti-enflamatuvar etkisinden dolayı yaygın olarak kullanılmaktadır. Kolşisin uygun konsantrasyonlarda oral yolla kullanılmakta iken yüksek konsantrasyonlarda toksik etki gösterdiği tespit edilmiştir. Bu nedenle, kanser araştırmalarında düşük doz kolşisinin etki mekanizmaları üzerine çalışmalar yapılmaktadır. Matriks metalloproteinaz-2 (MMP-2), matriks metalloproteinaz enzim ailesinin bir üyesi olup kanserde ifade seviyesinin arttığı ve ekstrasellüler ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Colchicine and quercetin were used as positive controls for A431 cells. Earlier data reported that colchicine induces cell cycle arrest at the G2/M phase in MCF-7 cells [ 49 ], while quercetin causes cell cycle arrest in the S-phase [ 50 ]. Our data confirmed these reports, as colchicine significantly inhibited cell viability at a concentration of 50 nM by inducing cell cycle arrest at the G2/M phase (74%) in A431 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Colchicine and quercetin were used as positive controls for A431 cells. Earlier data reported that colchicine induces cell cycle arrest at the G2/M phase in MCF-7 cells [ 49 ], while quercetin causes cell cycle arrest in the S-phase [ 50 ]. Our data confirmed these reports, as colchicine significantly inhibited cell viability at a concentration of 50 nM by inducing cell cycle arrest at the G2/M phase (74%) in A431 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of colchicine against human breast adreno-carcinoma MCF-7 cells demonstrated that colchicine induced the cell cycle arrest at the G2/M phase of mitosis along with down-regulation of MMP-2 mRNA expression in MCF-7 cells [ 89 ].…”
Section: Anticancer/cytotoxic Potential Of Alkaloids: Pharmacological...mentioning
confidence: 99%